Importance and Effects of Islamic Creedon Individual and Society in Surah Al-Rum - Al-Muhammadi, Ammar Zaid Khalaf; Jubeir Al-Jubouri , Ahmed Abdul-Razzaq (International Journal of Psychosocial Rehabilitation, 2020)
This research includes the statement of the Islamic creed as the basis upon which all the laws of religion are built. Holy Qur’an will remain the holly book of the great guidance that guarantees all human needs in the belief, worship, behavior, businesses and other matters of religion and the world. The research set out to explain the importance of this belief and its impact on the individual and society in one of the makiya chapters of Holly Qur’an, namely Surah Al-Roum.